Role of positive glucose challenge test only versus oral glucose tolerance test in pregnancy outcome: a comparative study (Journal of Pathology of Nepal, 2019)
Background: Gestational diabetes mellitus is defined as any degree of glucose intolerance which is first recognized during pregnancy and is associated with a number of adverse perinatal outcomes, such as neonatal hypoglycemia, macrosomia with an increased risk of shoulder dystocia and the need for neonatal intensive care. Maternal complications include pre-eclampsia and an increased risk of caesarean delivery. The objective of this study was to compare maternal and perinatal outcomes in pregnant women with positive and negative oral glucose tolerance test following positive glucose challenge test.Materials and Methods: This is a prospective observational hospital based study of 120 patients admitted in Nobel Medical College Teaching Hospital, Biratnagar with glucose challenge test positive pregnancy for delivery. Oral glucose tolerance test was performed in all the glucose challenge test positive pregnant and compared with various maternal parameters and newborn’s conditions.Results: Among 120 patients included in the study, 28 (30.4%) cases were oral glucose tolerance test. Pregnancy induced hypertension was present in 12 cases. Hyperbilirubinemia was present in 42, hypoglycemia in 32, respiratory distress in 44, birth asphyxia in 15 and macrosomia in 6 cases.Conclusions: Pregnancy induced hypertension and hyperbilirubinemia were found to be significantly higher in OGTT positive cases so early detection of GDM screening via is advisable